Reduction in mortality and teratogenicity following simultaneous administration of folic acid and vitamin E with antiepileptic, antihypertensive and anti-allergic drugs - Shahana Wahid; Rafeeq Alam Khan; Zeeshan Feroz (Wolters Kluwer Medknow Publications, 2014)
Aim: The present study was designed to evaluate the teratogenic effects on breeding pattern in mice following administration of lamotrigine (LT) and levetiracetam (LV) and its combination with anti-hypertensive and anti-allergic drugs. Moreover, possibility of decrease in teratogenic effect was also evaluated upon simultaneous administration of these combinations with folic acid or vitamin E. Materials and Methods: The study was carried out on mature female mice housed in polycarbonate breeding cages. Drugs were administered continuously till the birth of neonates and pups were examined for any teratogenic potential of drugs. Results: The results of the study reveals that teratogenic effects of lamotrigine, methyldopa and loratadine (LTMLO) combination were seems to be reduced upon simultaneous administration with folic acid, while addition of vitamin E was found to be more effective in reducing the mortality rate of levetiracetam, methyldopa and loratadine combination. Conclusion: Teratogenic effects of LTMLO combination were better prevented by folic acid. However, further studies on large number of animals and humans are required before reaching to definite conclusion.